2019
DOI: 10.1186/s12913-019-4781-y
|View full text |Cite
|
Sign up to set email alerts
|

Significant influencing factors and practical solutions in improvement of clinical nursing services: a Delphi study

Abstract: BackgroundClinical services evaluation with specific indicators are very helpful to identify improvable points. This study was conducted to analyze the factors affecting the quality of clinical nursing services and offer practical solutions for accreditation of clinical nursing services.MethodsThe present study was conducted using Delphi method with two rounds. At the beginning of the study a questionnaire was prepared using results of another project (clinical nursing services audit). This questionnaire was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…indicated that a nurse's performance is associated with the rules or measures that govern them. As suggested by Poortaghi et al., 22 it is necessary to develop a regulatory measure for the performance of head nurses. This is because an effective performance assessment can determine their strengths and weaknesses, and develop their management and leadership 2 .…”
Section: Discussionmentioning
confidence: 99%
“…indicated that a nurse's performance is associated with the rules or measures that govern them. As suggested by Poortaghi et al., 22 it is necessary to develop a regulatory measure for the performance of head nurses. This is because an effective performance assessment can determine their strengths and weaknesses, and develop their management and leadership 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' assessment of the QNC can encourage them to develop their practical skills, pinpoint weaknesses, guarantee that services are provided properly and eliminate defects and dissatisfaction in the units, which will ultimately result in greater motivation for giving higher quality services and meeting the patients' needs (Poortaghi et al, 2020). Since it is never possible to achieve very great quality, it is essential that quality be assessed constantly (Esmaeilpourzanjani & Mashouf, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since the nurses are constantly in close contact with the patients, decision making and giving moral comments are inseparable parts of their responsibility. 1 It can also be said that the nursing profession is based on ethics and many nurses consider professional ethics in their work environment. 2 However, some nurses may not have the power and support to do the right thing and sometimes do not even know what to do.…”
Section: Introductionmentioning
confidence: 99%